Post a New Question

Math Sequence

posted by .

the nth term of a series is 9n-7. what is the result of subtracting the kth term from the (k+1)th term?

(with solution pls, thnx)

  • Math Sequence -

    looks like we can just substitute and evaluate

    term(n ) = 9n-7

    term(k+1) = 9(k+1) - 7 = 9k + 2
    term(k) = 9k - 7

    so term(k+1) - term(k)
    = 9k+2 - (9k-7) = 9

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question